Location of rectal cancer as determined using rectal magnetic resonance imaging, and its relationship with pulmonary metastasis - Han, Na Yeon; Kim, Min Ju; Park, Beom Jin; Sung, Deuk Jae (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The aim of this study was to evaluate the accuracy of 3-T magnetic resonance imaging (MRI) in locating rectal cancer, and to determine whether tumor location correlates with the incidence of pulmonary metastasis. Materials and Methods: A total of 146 patients with confirmed rectal adenocarcinoma underwent 3-T rectal MRI, and abdominal and chest computed tomography (CT) within 2 weeks of the endoscopic examination. We reviewed the distance between the mass and the anal verge recorded in the endoscopic reports of these patients. Two radiologists evaluated the same distance on MRI scans by using picture archiving and communications systems. Multiple factors including the tumor location, primary tumor and lymph node stage, lung and liver metastasis, pathologic differentiation, and the carcinoembryonic antigen level were evaluated. The correlation between tumor location on MRI and endoscopy was assessed, and significant factors influencing pulmonary metastasis were identified using multivariate logistic regression analysis. Results: There was a statistically significant correlation between the tumor location established using MRI and the actual location recorded during endoscopy. The incidence of pulmonary metastasis was significantly higher in patients with lower rectal cancer (11/17, 65%) compared to those with upper rectal cancer (6/17, 35%; p<0.05). Factors associated with pulmonary metastasis were tumor location and the presence of liver metastasis. Conclusion: The accurate tumor location could be indicated using 3-T rectal MRI. Pulmonary metastasis occurred more frequently in patients with lower rectal cancer than in those with upper rectal cancer.